Strong but not Unbeatable: Two Cases of Healed Severe Skull Trauma in Males Buried in Medieval Mass Graves (Kutná Hora-Sedlec, Czech Republic) - Hana Brzobohatá; Filip Velímský; Jan Frolík (Fasciculi Archaeologiae Historicae)
This paper presents two cases of healed skull trauma recovered from medieval mass burial sites in Kutná Hora-Sedlec (Kutná Hora District/CZ). These recently unearthed burial pits are historically and contextually associated with two key catastrophes: (1) a famine in the early 14th century; and (2) the Black Death in the mid-14th century. The first skull presents evidence of survival from severe cranial injury with highly probable surgical intervention. The second one presents evidence of successful skull surgery, confirming the practice of trepanation performed by a skilled specialist in a given region at a given time in history. Although both individuals had been robust enough to withstand the pain and strain of the treatment, indicating considerable resilience to survive the skull trauma, they succumbed to mass infection or famine that killed a large number of inhabitants of this prominent medieval mining region.